IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 46 TAHUN 2011 TENTANG PENILAIAN PRESTASI KERJA PEGAWAI NEGERI SIPIL DI KABUPATEN SERUYAN PROVINSI KALIMANTAN TENGAH - Addeli Addeli; Hardi Warsono (Dialogue : Jurnal Ilmu Administrasi Publik, 2019)
Assessment or evaluation on the performance of an employee is a very importantpart to know the quality of work and behavior in carrying out the duties of service to thecommunity. Therefore it is appropriate if the Government issued Government RegulationNumber 46 Year 2011 on Employee Performance Appraisal which in it regulates theassessment of employee performance based on Employee Work Objectives (SKP) andEmployee Work Behavior. The irony is that Seruyan Regency has implemented thisGovernment Regulation from 2014 until now, but it is still far from what is expected byGovernment Regulation Number 46 Year 2011 on Job Performance Appraisal of thisEmployee. This phenomenon underlying for qualitative research using theImplementation Model of Government Regulation No. 46 of 2011 on EmployeePerformance Appraisal in Seruyan Regency using George C. Edward III theory whichsees the implementation process through Communication, Resources, Disposition andOrganizational Structure as well as policy content. The result of the research shows thatthere are still many employees who have not understood and acknowledged about theperformance appraisal and the absence of supervision made causing the implementationof government regulation is not running according to the regulation. Factors that hamperthe implementation of this policy include the number of personnel Personnel Agency andHuman Resources Development (BKPSDM) Seruyan District is very minimal in theprocess of disseminating and training this policy and the absence of Standard Operating(SOP) in the implementation of the field that causes the implementers and recipients tobe not focus.